In Vitro Activity of Ibrexafungerp against a Collection of Clinical Isolates of Aspergillus, Including Cryptic Species and Cyp51A Mutants, Using EUCAST and CLSI Methodologies - Rivero-Menendez, Olga (J Fungi (Basel), 2021)
Ibrexafungerp is a new orally-available 1,3-β-D-glucan synthesis inhibitor in clinical development. Its in vitro activity and that of amphotericin B, voriconazole, and micafungin were evaluated against a collection of 168 clinical isolates of Aspergillus spp., including azole–susceptible and azole–resistant (Cyp51A mutants) Aspergillus fumigatus sensu stricto (s.s.) and cryptic species of Aspergillus belonging to six species complexes showing different patterns of antifungal resistance, using EUCAST and CLSI antifungal susceptibility testing reference methods. Ibrexafungerp displayed low geometric means of minimal effective concentrations (MECs) against A. fumigatus s.s. strains, both azole susceptible (0.040 mg/L by EUCAST and CLSI versus 1.231 mg/L and 0.660 mg/L for voriconazole, respectively) and azole resistant (0.092 mg/L and 0.056 mg/L, EUCAST and CLSI, while those for voriconazole were 2.144 mg/L and 2.000 mg/L). Ibrexafungerp was active against most of the cryptic species of Aspergillus tested, yielding MEC values only comparable to those of micafungin. Nevertheless, this new compound exhibited a moderate activity against A. ustus complex species, MECs ≥ 0.5 mg/L against Aspergillus insuetus and Aspergillus keveii strains, and was inactive against the Aspergillus alliaceus isolates tested (MEC(90)s ≥ 16 mg/L). All in all, ibrexafungerp shows encouraging in vitro results against cryptic species of Aspergillus and azole–susceptible and azole resistant strains of A. fumigatus, some of which are difficult to treat using the available therapeutic options.